Exposure to noise and ototoxic chemicals in the Australian workforce. Issue 5 (25th January 2019) - Lewkowski, Kate; Heyworth, Jane S; Li, Ian W; Williams, Warwick; McCausland, Kahlia; Gray, Corie; Ytterstad, Elinor; Glass, Deborah C; Fuente, Adrian; Si, Si; Florath, Ines; Fritschi, Lin
Abstract : Objective: To determine the current prevalence of exposure to workplace noise and ototoxic chemicals, including co-exposures. Method: A cross-sectional telephone survey of nearly 5000 Australian workers was conducted using the web-based application, OccIDEAS. Participants were asked about workplace tasks they performed and predefined algorithms automatically assessed worker's likelihood of exposure to 10 known ototoxic chemicals as well as estimated their full shift noise exposure level (LAeq, 8h ) of their most recent working day. Results were extrapolated to represent the Australian working population using a raked weighting technique. Results: In the Australian workforce, 19.5% of men and 2.8% of women exceeded the recommended full shift noise limit of 85 dBA during their last working day. Men were more likely to be exposed to noise if they were younger, had trade qualifications and did not live in a major city. Men were more likely exposed to workplace ototoxic chemicals (57.3%) than women (25.3%). Over 80% of workers who exceeded the full shift noise limit were also exposed to at least one ototoxic chemical in their workplace. Conclusion: The results demonstrate that exposures to hazardous noise and ototoxic chemicals are widespread in Australian workplaces and co-exposure is common. Occupational exposure occurs predominantly for men and could explain some of the discrepancies in hearing loss prevalence between genders.